2012
DOI: 10.11594/jtls.02.03.09
|View full text |Cite
|
Sign up to set email alerts
|

Earthworm Population Density in Sugarcane Cropping System Applied with Various Quality of Organic Matter

Abstract: Earthworms population in the soil are greatly impacted by agricultural management, yet little is known about how the quality and quantity of organic matter addition interact in sugarcane cropping system to earthworm population. This study describes the effect of various organic matter and application rates on earthworms in sugarcane cropping system. Earthworms were collected in April, July and December from 48 experimental plots under five kinds of organic matter application : (1) cattle manure, (2) filter cak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
5
1
1
Order By: Relevance
“…Experimental research conducted in sugarcane fields in Malang Regency showed that earthworms will be found in areas with high organic matters (Nurhidayati et al, 2012), but this condition was not found in this study. However, research conducted in the peat forest in Central Kalimantan showed a similar result, where the area with a high litter thickness was not a preferred habitat for earthworms (Maftu'ah & Susanti, 2009).…”
Section: Resultscontrasting
confidence: 75%
See 1 more Smart Citation
“…Experimental research conducted in sugarcane fields in Malang Regency showed that earthworms will be found in areas with high organic matters (Nurhidayati et al, 2012), but this condition was not found in this study. However, research conducted in the peat forest in Central Kalimantan showed a similar result, where the area with a high litter thickness was not a preferred habitat for earthworms (Maftu'ah & Susanti, 2009).…”
Section: Resultscontrasting
confidence: 75%
“…In Indonesia, research on earthworms has not been widely conducted, especially those related to their indirect benefits on a spring's conservation. Earthworm research in Indonesia was mostly related to their benefits to the agricultural area (Nurhidayati, Arisoesilaningsih, Suprayogo, & Hairiah, 2012), earthworm as bioindicator on polluted soil (Joko, Anggoro, Sunoko, & Rachmawati, 2017), and their benefit to reclamation in the mining area (Nugroho, Widuri, & Sayektiningsih, 2018). The activity of earthworms will also benefit the absorption of rainwater into the soil which will maintain the groundwater and water flow regulation (Dewi & Senge, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The Climograph drawn during the sugarcane growth season has confirmed that the first sampling took place during the dry season, a period of low rainfall (Figure 2). At the sugarcane area, the negative effect on taxa diversity was worse due to the recent crop harvest with burning of harvest residues (Portilho et al, 2011;Nurhidayati, 2012). Soil macrofauna communities at the Atlantic forest area, situated in the upland part of the study area, were more affected by climatic conditions than the Sandbank ones.…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, soil tillage is traditionally with use of various agricultural machinery mainly made with disc plows, dish harrows and subsoilers (Portilho et al, 2011;Tavares et al, 2015;Surendran et al, 2016) that negatively affect soil aggregation and reduce biological activity (Benito et al, 2008). In addition to modifying soil physico-chemical characteristics, sugarcane cultivation also produces environmental chemical contamination and soil compaction (Iwai et al, 2008;Nurhidayati et al, 2012;Siqueira et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Di Ethophia, penambahan kompos 15 ton/ha dan 46 kg N/ha dapat meningkatkan kadar C, N, P dan K tanah liat, serta produksi dan rendemen tebu (Thesome et al, 2014). Pada lahan tebu di Malang Selatan, Jawa Timur, penambahan bahan organik berupa pupuk kandang, seresah tebu dan blotong dapat meningkatkan populasi cacing tanah dan mikrorganime tanah (Nurhidayati et al, 2012).…”
Section: Pengaruh Bahan Organik Terhadap Sifat Kimia Tanahunclassified